Answer:
Below
Step-by-step explanation:
Substituting the given values:
f(6) = 6(2/3) - 2 = cube root of 6^2 - 2 = cube root 36 - 2
f(-6)= (-6)(2/3) - 2 = cube root of(-6)^2 - 2 = cube root 36 - 2
So This is true,
f(6) = cube root of 6^2 - 2 = cube root 36 - 2 = 1.3019
2 * f(3) = 2 * (cube root of 3^2 - 2 ) = 2 * (cube root of 9 - 2) = 0.1602
So False,
Answer:3 boxes.
Explanation: $21 / $7=3 boxes
Answer:
radius
Step-by-step explanation:
i believe it is radius because in my point of view it looks like the line travels up to the half of the circle.
10 and -4. You multiply 10 times -4 to get -40 and you add 10 and -4 to get 6
Answer:
Step-by-step explanation:
180